Інформаційні технології як імпакт-фактор в економіці України - Дмитрієва, Вікторія Анатоліївна; Dmytriieva, Viktoriia (Дніпровський державний технічний університет, 2025)
Інформаційні технології в сучасній економіці відіграють роль рушійної сили, яка розвиває спосіб ділової та соціальної комунікації, модернізує засоби збору, збереження, обробки та поширення інформації, спричиняє появу нових форм бізнес діяльності, прискорює процеси прийняття рішень та, врешті-решт, змінює стиль життя населення країни. Суспільство, яке ігнорує розвиток новітніх технологій та відмовляється впроваджувати їх у життя, приречене на регрес. Саме винайдення та застосування новітніх технологій дозволяло людству виходити з глибоких економічних криз та депресій, надаючи можливості для створення нових форм ділової активності, способів підвищення якості продукції та прибутковості, розвитку науки та підйому економіки. Сучасний етап розвитку людства названо «інформаційним», оскільки після попередніх технологічних циклів саме інформаційні технології почали змінювати соціальні та економічні принципи взаємодії у суспільстві. В цій статті, з використанням даних Державної служби статистики України та Світового Банку, представлено, які саме трансформації в Україні спричиняють інформаційні технології. Information technologies play a crucial role in contemporary economy that develop ways for business and social communication, modernize tools of collect, analysis and share of information, cause appearance of new forms of business activity, force processes of decision-making and amend lifestyle of country population. Society that ignores the development of new technologies and refuses to implement them into life is doomed to stagnation. Just invention and application of innovative technologies allow countries to overcome the deep crisis and depression, giving people opportunities for creation of new forms of economic activity, means to improve products quality and increase profitability, science development and economic growth. The current stage of human development is called "informational" because, after previous technological cycles, it was information technologies that began to change the social and economic principles of interaction in society. At the same time, they remain expensive and inaccessible to most companies and customers. Because of this, some processes of informatization can proceed slowly. This article, using data from the State Statistics Service of Ukraine and the World Bank, presents what transformations in Ukraine are caused by information technologies. To gain this aim, data for the period of 2005-2023 were studied and as a result graphical analysis was conducted for some key indicators of information technologies application. There are such parameters as share of people in the population who use Internet technologies; volume of sales (goods, services) of enterprises received from e-commerce (thousands of UAH); share of the number of enterprises whose employees have remote access in the total number of enterprises by access capabilities; share of enterprises that conducted Big Data analysis in appropriate ways; share of the number of enterprises that had a website in the total number of enterprises by website functionality; share of the number of enterprises that applied ICT security measures in the enterprise's information and communication systems in the total number of enterprises; share of enterprises in Ukraine that hired IT specialists or provided training in relevant areas
Information technology as an impact factor in the economy of Ukraine
Keywords: електронний бізнес; e-business; цифрові комунікації; digital communications; інформаційна система; information system; хмарні технології; cloud technologies; економічний розвиток; economic development